IMPLIKASI PEMBELAJARAN BERBASIS HUMANISTIK PADA PADA PENDIDIKAN AGAMA ISLAM - Rulitawati Rulitawati; Purmansyah Ariadi; Yuniar Handayani; Sri Yanti (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
Abstract Learning carried out by an educator has certain characteristics so that teachers in packaging learning require skills and theories in learning so that reasoned learning can be accepted by students. The purpose of this study is to describe